2018
DOI: 10.7717/peerj.5295
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heavy metals on the viability of Tetraselmis marina AC16-MESO and an evaluation of the potential use of this microalga in bioremediation

Abstract: The use of microalgae in biotechnological processes has received much attention worldwide. This is primarily due to the fact that they are inexpensive to grow, requiring only sunlight and CO2, whilst lending themselves to a range of uses, such as to reduce CO2 levels, as fish feed, in biofuel production, for the generation of secondary metabolites of interest, and in bioremediation. These features mean that microalgae are excellent candidates for the implementation of a range of eco-friendly technologies. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…With the growth of industrial, mining and economic activities, surface water quality is facing enormous challenges (Islam et al, 2015;Vörösmarty et al, 2010). Among challenges, heavy metal contamination is of particular concern (Ariffin et al, 2017;Burakov et al, 2018;Cameron, Mata & Riquelme, 2018;Islam et al, 2015). Dissolved heavy metals in water could readily enter the food chain, which eventually leads to serious health risks to ecosystems and humans (Nguyen et al, 2018;Rehman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the growth of industrial, mining and economic activities, surface water quality is facing enormous challenges (Islam et al, 2015;Vörösmarty et al, 2010). Among challenges, heavy metal contamination is of particular concern (Ariffin et al, 2017;Burakov et al, 2018;Cameron, Mata & Riquelme, 2018;Islam et al, 2015). Dissolved heavy metals in water could readily enter the food chain, which eventually leads to serious health risks to ecosystems and humans (Nguyen et al, 2018;Rehman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, microalgae have emerged as a promising biosorbent for water treatment due to the presence of a high number of functional groups in their cell wall that contribute to the removal of toxic elements from water in a simple, efficient, and economic manner (Zeraatkar et al, 2016). Previous studies have demonstrated the ability of microalgae species to adsorb HM ions from water, which confirms their high bioremediation potential (Cameron et al, 2018;Torres et al, 2017). For instance, a metal biosorption of 22.3 mg Zn (II)/g was obtained in a solution with 150 mg Zn/L, using the green microalgae Scenedesmus obliquus (Monteiro et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…With the growth of industrial, mining and economic activities, surface water quality is facing enormous challenges (Islam et al 2015;Ustaoğlu et al 2020a;Vörösmarty et al 2010). Among challenges, heavy metal contamination is of particular concern (Ariffin et al 2017;Burakov et al 2018;Cameron et al 2018;Islam et al 2015). Dissolved heavy metals in water could readily PeerJ reviewing PDF | (2020:03:46588:1:1:NEW 29 Jun 2020)…”
Section: Introductionmentioning
confidence: 99%